Spatiotemporal Dynamics of Mangrove Cover in Aceh Tamiang Regency, Indonesia (2020–2024): An NDVI-Based Remote Sensing Assessment - Cut Maila Hanum; Kamal, Alfarazi; Metananda, Arya A.; Kurniawati; Dedi Kiswayadi; Bakruddin (UIR PRESS, 2026)
This study examines spatiotemporal changes in mangrove cover and canopy density in Aceh Tamiang Regency, Indonesia, between 2020 and 2024, using an integrated remote sensing and field-based approach. High-resolution PlanetScope imagery (3 m) and Sentinel-2A data (10 m) were analyzed within a GIS framework, with the Normalized Difference Vegetation Index (NDVI) employed to classify mangrove density into three categories: dense (NDVI ≥ 0.43), moderate (0.33 ≤ NDVI < 0.43), and sparse (NDVI < 0.33). Results reveal a net loss of 379.65 hectares of mangrove cover—declining from 10,796.76 ha in 2020 to 10,417.11 ha in 2024—with over 99% of deforestation occurring in production forest zones, primarily due to conversion for aquaculture and oil palm plantations. Concurrently, dense mangrove areas decreased by 2,226 hectares (–18.9%), while sparse mangrove coverage expanded by 1,542 hectares (+28.1%), signaling ecosystem degradation despite localized natural regeneration. These structural changes undermine critical ecological functions, including coastal protection, blue carbon storage, and habitat provision for species such as Batagur borneoensis. The findings underscore the urgent need to integrate satellite-derived monitoring into district-level spatial planning, prioritize community-based rehabilitation in transitional zones, and strengthen enforcement of mangrove protection under Indonesia’s Government Regulation No. 27 of 2025 to ensure long-term coastal resilience.